The enhanced polymer-coated graphite anode electrodes for the electrooxidation of glucose - Aykut Çağlar (MANAS: Journal of Engineering)
In this study, poly(N-Isopropylacrylamide) (PNIPAM), poly(acrylamide) (PAAM), poly(acrylic acid) (PAAc), and poly(methacrylic acid) (PMAc) polymers are synthesized by radical polymerization method. The chemical composition and surface morphology of the PMAc polymer are examined by micro-Raman spectroscopy and scanning electron microscopy (SEM). The electrochemical measurements are examined by cyclic voltammetry (CV), chronoamperometry (CA), and electrochemical impedance spectroscopy (EIS) analyses for glucose (Glu) electrooxidation. The characterization analyses reveal that the polymer structure was formed. The electrochemical analysis results indicate that the PMAc/G electrode has higher catalytic activity, stability, and resistance compared to other electrodes with a specific activity of 1.7 mA/cm2.